The Response of the Red Morph of the Tobacco Aphid, Myzus Persicae Nicotianae, to Insecticides Applied under Laboratory and Field Conditions - Rhoda , Masukwedza; Mazarura, Upenyu; Peter , Chinwada; Susan , Dimbi (Asian Journal of Agriculture and Rural Development, 2013)
The tobacco aphid, Myzus persicae nicotianae is an economically important pest of tobacco, causing extensive yield losses especially as it is an important host of numerous viruses and the sudden shift from the green morph to the red morph is of concern as reports of insecticide resistance are common in this morph. The efficacy of several insecticides was studied, both in the laboratory and in the field, to establish the pest status of the red coloured morph of the tobacco aphid with respect to resistance build up. The laboratory tests confirmed that resistance could be of concern in Monocrotophos only and the field work appeared to show some build up of resistance additionally in Aldicarb. The results point at a need for continued monitoring as well as use of rotations in chemical use in order to reduce the chance of resistance build up.